Assessment of Patients' Views on Drug Benefits and Risks: An Interview Study with Cardiovascular Patients. (14th November 2022) - Wakob, Ines; Wintsche, Ina; Frisch, Annett; Remane, Yvonne; Laufs, Ulrich; Bertsche, Thilo; Schiek, Susanne
Abstract : Better and balanced information strategies supporting cardiovascular patients' adherence are required. Cardiovascular drugs have outstanding morbidity and mortality benefits. This can be counteracted by patients' perceptions of risks. Drug information should help the patient but not fuel unwarranted fears. We performed a cross-sectional survey of patients admitted to a cardiology ward. We evaluated (i) the patients' general benefit-risk estimation of their pharmacotherapy; (ii) views on benefits; (iii) views on risks; and (iv) information sources. Additionally, we assessed aspects of anxiety and depression with the Patient Health Questionnaire-4 (PHQ-4). (i) 67 patients (66%) rated expected drug benefits higher than potential risks. (ii) 72% of benefits motivated the patients to take their medication as prescribed. Patients more frequently mentioned surrogate markers as benefits than clinical benefits (p < 0.001 ). (iii) 56% of risks mentioned were perceived as bothersome and 35% as concerning. Risks were more often perceived as bothersome and concerning by patients with higher PHQ-4 scores (p = 0.016 ). (iv) Physicians were the most frequent information source of benefits (92% of patients) and risks (45%), and pharmacy staff for 27% and 14%, respectively. Laymen or media served as sources of information on benefits in 39%, for risks in 40%, and package leaflets in 26% and 36%. 42% of the patients would like to receive more information on benefits versus 27% on risks. Our results suggest that knowledge of benefits motivates patients to take their drugs as prescribed. There is already good information on surrogate markers for process control with active patient involvement. However, a lack of knowledge still exists in relation to clinical benefits. Regarding risks, it has been shown that patients with higher PHQ-4 scores are more likely to be bothered or concerned. Both emphases on clinical benefits and individualization depending on PHQ-4 scores may be valuable resources for patient counseling to support adherence.